Combination therapy with angiotensin converting enzyme inhibition and AT1 receptor inhibitor ventricular remodeling after myocardial infarction in rats - Zornoff, Leonardo A.M. [UNESP]; Paiva, Sérgio A.R. [UNESP]; Matsubara, Beatriz B. [UNESP]; Matsubara, Luiz S. [UNESP]; Spadaro, Joel [UNESP] (SAGE Publications, 2000)
Background: There are limited data regarding the effects of angiotensin II receptor blockade after myocardial infarction (MI). In addition, whether combined angiotensin converting enzyme (ACE) inhibitor and angiotensin II type I (AT1) receptor antagonist may be superior to either drug alone on ventricular remodeling remains unclear. The goal of this study was to determine if the cardiac effects of the combined administration of an ACE inhibitor and AT1 receptor antagonist are greater than those produced by either of these agents administered individually after MI. Methods and Results: After MI, rats were divided into 4 groups: 1) untreated animals, 2) lisinopril treatment (20 mg/kg/day), 3) losartan treatment (20 mg/kg/day), and 4) lisinopril plus losartan treatment. After 3 months, the cardiac parameters studied were: mortality, fibrosis (hydroxyproline), hypertrophy (ventricular weight/body weight ratio [VW/BW]), left ventricular enlargement (volume at end-diastolic pressure equaled zero/body weight ratio [VO/BW]), and ventricular function (isovolumetric developed pressure, dp/dt, -dp/dt). A lowest mortality rate in the animals treated with the combination of both ACE inhibitor and AT1 receptor antagonist was observed. Although lisinopril and losartan significantly decreased VW/BW ratio, when administered concomitantly, VW/BW ratio was lower than when either agent was administered individually. There were no differences in right ventricle hydroxyproline concentration. Only combination therapy decreased VO/BW ratio. The treatment with lisinopril plus losartan resulted in increases in the development of pressure versus untreated group; without alteration in dp/dt and -dp/dt. Conclusions: The combination of the AT1 receptor blockade and ACE inhibitor is more effective than individual treatment on ventricular remodeling and survival after MI in rats.
Keywords: Lisinopril; Losartan; Mortality; Myocardial ischemia